Blended and Online Learning for Global Citizenship: New Technologies and Opportunities for Intercultural Education - Hunter, William J.; Austin, Roger (Routledge Research in International and Comparative Education, 2021)
By showcasing international, European, and community-based projects, this volume explores how online technologies using collaborative and blended learning can be used to bolster social cohesion and increase students’ understanding of what it means to be a global citizen. With the pace of technology rapidly increasing, Blended and Online Learning for Global Citizenship draws timely attention to the global lessons being learned from the impact of these technologies on peace building, community development, and acceptance of difference. In-depth case studies showcasing successful projects in Europe, Northern Ireland, and Israel explore blended learning and illustrate how schools and educators have embraced online technologies to foster national and international links both within and beyond communities. This has, in turn, equipped students with experiences that have informed their attitudes to cultural and political conflicts, as well as racial, ethnic, and social diversity. Building on the authors’ previous work Online Learning and Community Cohesion (2013), this thought-provoking text will be of interest to researchers, academics, and postgraduate students in the fields of international and comparative education. Educators and school leaders concerned with how multiculturalism and technology play out in the classroom environment will also benefit from reading this text.